LIPID COMPOSITION IN GONADS OF BARYTELPHUSA CUNICULARIS DURING DIFFERENT SEASONS - NAYAB ANSARI, (International Journal of Pharma and Bio Sciences, 2013)
The knowledge of biochemical compositions f any edible organism is extremely important. Since the nutritive value is reflected in its biochemical content. Lipid storage is advantageous to organisms since it can deliver eight times more calories per unit weight of energy to that from carbohydrates . During reproductive seasons lipids along with glycogen are channelled towards the gonads to meet the cost of active gametogenesis in crustaceans. The present study shows that the lipid content of Barytelphusa cuncularis to be more in gonads during winter (gonadal growth stage) and least during summer (spent stage).